The Microfoundations of Mission-Led Interdisciplinary Collaborations: The Role of Design Principles - Rabello, RCC; Ruckstuhl, K; Woodfield, P; Kokshagina, O; Sandretto, S (Wiley, 2023)
Mission-oriented (MO) research aims to address social, economic and policy goals through an agreed and evidence-based set of ‘missions’. Vital to achieving a mission are bottom-up and cross-organisational interdisciplinary collaborations. However, these collaborations are often time and resource intensive. Paying attention to microfoundation behaviours can elucidate the individual capabilities required for mission-oriented science. Design-driven approaches have proven useful in supporting the microfoundations of interdisciplinary collaborations. However, we know little about what design principles support MO research. To understand this, we conducted a workshop built on a Concept-Knowledge (C-K) design principles as part of a longitudinal study of a mission-oriented interdisciplinary science innovation programme in New Zealand. Our results indicated that the C-K principles of knowledge mapping, concept exploration and mindful deviation enhanced workshop participants' willingness to creatively experiment across disciplines, provided a shared research directionality and addressed many of the barriers identified in the longitudinal study. We argue that our findings complement and deepen empirically driven microfoundational research by unpacking the specific role of design principles in inducing the behaviours that are essential to advancing large-scale mission-oriented research collaborations.
Keywords: 3503 Business Systems In Context; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Generic health relevance; 1503 Business and Management; Business & Management; 3503 Business systems in context; 3507 Strategy, management and organisational behaviour